Immune Response After Rabies Vaccination in Owned Free-Roaming Domestic Dogs in Flores Island, Indonesia - Wera, Ewaldus; Warembourg, Charlotte; Bulu, Petrus M.; Siko, Maria M.; Dürr, Salome (Frontiers in Veterinary Science, 2022)
Vaccination is the main tool to prevent the circulation of rabies in dog populations. The development of an immune response after vaccination differs between individual dogs and depends on many factors. Here, we first investigated the level of, and associated factors for, the presence of binding antibodies in 130 healthy dogs from Flores Island, Indonesia. Secondly, we identified factors associated with the development of binding antibodies within 30 days after vaccination among dogs that had a binding antibody titre <0.5 EU/ml at the day of vaccination (D0, N=91). Blood samples were collected from the individual dogs immediately before vaccination at D0 and 30 days after vaccination (D30). The rabies antibody titres were determined using Enzyme-linked immunosorbent assays. Information on potential risk factors such as the dog’s age and sex, history of vaccination, type and frequency of feeding, and BCS (body condition score) were gathered during interviews at D0. Regression analyses were performed to identify the risk factors associated with the presence of binding antibody titre ≥ 0.5 EU/ml at D0 for the 130 dogs and the development of binding antibody titre ≥ 0.5EU/ml at D30 for the 91 dogs. The results showed that the proportion of dogs with antibody titre ≥0.5 EU/ml was 30.0% (39/130) at D0. The only factors found to be significantly influencing the presence of binding antibodies titres ≥0.5 EU/ml was previous vaccination within one year before D0 (46.8% versus 14.7%, Odds ratio (OR) = 3.6, 95%CI 1.5-9.3; p-value0.006), although the same trend was found for dogs of higher age and better BCS. Eighty-six percent (79/91) of dogs whose rabies binding antibody level was <0.5 EU/ml at D0 had developed an adequate immune response (≥0.5 EU/ml) at D30. Almost a significantly higher proportion developed an adequate immune response in dogs of good BCS compared to those of poor BCS (95.3% versus 79.2%, OR = 4.7, 95%CI 1.1- 32.5; p-value=0.057. Our findings show the high effectiveness of rabies vaccine in under field conditions to develop immunity and the importance of a good BCS, often achievable by good dog keeping conditions, for developing immunity after vaccination in dogs.